Human DNA sequences complementary to the small nuclear RNA U2. - Westin, G (1981)
Clones containing sequences complementary to the small nuclear RNA U2 were isolated from a human DNA library (1). Three clones, designated U2/4, U2/6 and U2/7 were purified and characterized by restriction enzyme cleavage, hybridization and heteroduplex analysis. Hybridization showed that the three clones each contained one single region which is complementary to U2 RNA. Restriction enzyme cleavage revealed furthermore that the inserted fragments in the three recombinants are different. Heteroduplex analysis identified a 240-380 bp long duplex region in each heteroduplex which includes sequences complementary to U2 RNA. Heteroduplexes between clones U2/4 and U2/7 as well as between U2/4 and U2/6 revealed two additional approximately 200 bp long homologies. The remainder of the inserts were found to lack measurable sequence homology. Two fragments from clone U2/4 were subcloned in the pBR322 vector and the subclones were used to determine the nucleotide sequence of a region in clone U2/4 which is complementary to U2 RNA. A comparison between the established sequence and the sequence for rat U2 RNA (2) reveals several discrepancies.